The Magic of Howl’s Moving Castle: An Analysis of Character Development in a Fantasy Novel - Mia Annisa Utami (Passage, 2018)
The present study aims to examine the influence of magical events on the development of the major character in the novel Howl’s Moving Castle by Diana Wynne Jones. The present study uses qualitative approach, particularly descriptive qualitative method. The data were collected by critically selecting the words, phrases, and sentences that reflect events with magical happenings. In analyzing the data, this study employs Nikolajeva’s (1988) magic laws and Tolkien’s (1966) functions of fantasy. The analysis reveals that the magical events influence the development of the main character through the magic laws, which portray certain functions of fantasy. The magic law that dominantly appears in the novel is consistency (i.e., the idea that the secondary world has rules that must be obeyed). Meanwhile, in terms of functions of fantasy, recovery (i.e., recapture the fundamental vision of things) becomes the dominant function primarily shown. The findings of the present study also indicate that, in the fantasy genre, the development of the character is triggered by the elements of surprise and the element of wonder presented in the novel. Keywords: character development, fantasy, magic, magical events